Isolation and Identification of Multi-antibiotic Resistant Aeromonas veronii by 16s rDNA Gene Sequencing from the Gut of Fresh Water Loach, Lepidocephalycthys guntea (Hamilton Buchanan) - Prasad Roy, Rudra; Bahadur, Min; Barat, Sudip (International Journal of Bio-resource and Stress Management, 2023)
An investigation was conducted to study the isolates of multiple antibiotic resistant Aeromonas sp. from the skin, gill and gut of fresh water loach, Lepidocephalichthys guntea (Hamilton Buchanan) from four different sites of river Lotchka in Darjeeling District, West Bengal, India. Isolated bacteria were identified by different biochemical procedures and Polymerase Chain Reaction (PCR) was performed using genus specific 16S rDNA primers for confirmation of identification of Aeromonas sp. Antibiotic susceptibility test of bacterial isolates was also done by Disc Diffusion method. A total of 18 Aeromonas sp. were isolated from skin, gill and gut of fish. Maximum resistance was exhibited for Penicillin-G, Ampicillin and Cephalothin (100%, 92% and 84% resistant in the gut of fish). In Ciprofloxacin and Tetracycline resistance was almost nil. Among all the isolates, one particular strain showed resistance against eight antibiotics. The bacterial strain was subjected to the PCR with Aeromonas genus specific 16S rRNA primers and the PCR product was sequenced. The sequence was performed by comparative analysis with the Genbank and maximum similarity was found with Aeromonas veronii. Presence of Aeromonas veronii resistance to multiple antibiotics indicated that the loach were contaminated with multi-antibiotic resistant enteric pathogenic bacteria.